2000
DOI: 10.1128/jcm.38.2.702-707.2000
|View full text |Cite
|
Sign up to set email alerts
|

Line Probe Assay for Monitoring Drug Resistance in Hepatitis B Virus-Infected Patients during Antiviral Therapy

Abstract: Since the introduction of antiviral compounds such as lamivudine and famciclovir in the treatment schedules of patients with chronic hepatitis B virus (HBV) infection, the accumulation of a variety of mutations in the HBV polymerase gene has been observed. The selection of these mutations is generally considered the cause of viral nonresponsiveness and treatment failure. Therefore, the detection of these mutations is of clinical importance. Previously genotyped HBV strains isolated from treated and untreated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(82 citation statements)
references
References 25 publications
2
77
0
3
Order By: Relevance
“…As already described in previous studies, the M552V mutant was found more frequently than the M552I mutant. [11][12][13][31][32][33] Interestingly, we found that in HBeAg-positive patients the M552I mutant was found either transiently or as a mixture with the M552V mutant suggesting that the M552V mutant had a replication advantage in this viral quasi-species, 13,21 while it was the predominant viral species in anti-HBe-positive patients infected with HBV genotype D. It will be interesting to see whether the pattern of mutation in the YMDD motif of the HBV polymerase is restricted by viral genotype on a larger number of patients. Moreover, we found that the C domain mutations were detected earlier than the B domain mutation in most of the patients, suggesting that the latter may represent a compensatory mutation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…As already described in previous studies, the M552V mutant was found more frequently than the M552I mutant. [11][12][13][31][32][33] Interestingly, we found that in HBeAg-positive patients the M552I mutant was found either transiently or as a mixture with the M552V mutant suggesting that the M552V mutant had a replication advantage in this viral quasi-species, 13,21 while it was the predominant viral species in anti-HBe-positive patients infected with HBV genotype D. It will be interesting to see whether the pattern of mutation in the YMDD motif of the HBV polymerase is restricted by viral genotype on a larger number of patients. Moreover, we found that the C domain mutations were detected earlier than the B domain mutation in most of the patients, suggesting that the latter may represent a compensatory mutation.…”
Section: Discussionmentioning
confidence: 75%
“…[27][28][29] To determine genotypic resistance and detect polymerase gene variability at codon 528 in the B domain of the reverse transcriptase, and at codons 552 and 555 of the C domain, a research LiPA was used as described previously in detail. 21 As the HBV polymerase gene has a different nucleotide length depending on genotypes, genotype A corresponding to the longest polymerase gene sequence was used as a reference for amino acid numbering.…”
Section: Determination Of Viral Genotypes and Detection Of Precore Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum on presentation was stored at Ϫ20°C then thawed to determine HBV genotype and precore and core promoter mutations. For determination of HBV genotype, HBV DNA was extracted as described by Stuyver et al 13 The HBsAg region spanning aa 107-205 was amplified and analyzed by the INNO-LiPA HBV Genotyping (Innogenetics NV, Gent, Belgium). The INNO-LiPA HBV Genotyping assay contained oligonucleotide probes specific for HBV genotypes A-G applied as 14 different lines on a membrane strip.…”
Section: Methodsmentioning
confidence: 99%
“…70 rtM204V can cause sI195W196 to change into either sM195W196 or sK195W196; and the rtM204I might result in sI195X196, sI195L196, sI195S196, or sT195L196. 70 It is clear that the different nucleotide changes selected during lamivudine therapy might affect HBsAg differently. The importance of these HBsAg amino acid changes needs further investigation, because mutations in HBsAg could have a significant impact on immune recognition, replication capacity, and virulence.…”
Section: Consequences For Hbsagmentioning
confidence: 99%